Tradisi dan Tata Cara Penanaman Tembuni Serta Selametan Bayi dalam Budaya Lampung - Alfina Fistalita; Mila Sari; Rahmat Prayogi; Bambang Riadi (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
The tradition of planting Tembuni (ari-ari) and preserving babies in Lampung culture is a form of local wisdom that still survives today, with a deep symbolic meaning as a hope for safety and happiness for newborn babies. This research aims to understand the meaning, spiritual values ​​and symbolism in the procession of planting tembuni and baby salvation. Qualitative research methods with an ethnographic approach were used through in-depth interviews with the community, traditional leaders and traditional birth attendants, as well as direct observation and literature review. The results of the research show that this tradition has a spiritual meaning that reflects a harmonious relationship with ancestors and nature, and is believed to have a positive influence on the baby's character as it is hoped that he will be a child who is respectful, not fussy, and has good luck in life. It can be concluded that this tradition not only contains spiritual and moral values, but also functions as social learning that strengthens the cultural identity and togetherness of the ultramodern Lampung community.